PENGARUH LITERASI DIGITAL DAN KECERDASAN EMOSIONAL TERHADAP KESIAPAN KERJA MAHASISWA: MOTIVASI KERJA SEBAGAI AGEN PENDORONG - Elistya Rimawati; Ari Wibowo; Wawan Laksito Yuly Saptomo; Cinthia Annisa Vinahapsari (JURNAL ILMIAH EDUNOMIKA, 2026)
The rapid advancement of digital technology has increased the demand for graduates who possess not only technical competencies but also strong psychological readiness for work. This study aims to examine the effects of digital literacy and emotional intelligence on students’ work readiness, with work motivation serving as a mediating variable. A quantitative approach was employed. Data were collected through an online questionnaire distributed to Information Systems and Informatics students who had completed Digital Transformation courses and were preparing for career entry. The data were analyzed using Partial Least Squares Structural Equation Modeling. The findings reveal that digital literacy and emotional intelligence have positive and significant effects on both work motivation and work readiness. Work motivation also significantly influences work readiness. Furthermore, work motivation partially mediates the relationships between digital literacy and work readiness, as well as between emotional intelligence and work readiness. The structural model demonstrates substantial explanatory power. These results suggest that digital literacy and emotional intelligence function as essential capabilities that can be transformed into actual work readiness when supported by strong work motivation. Therefore, higher education institutions should integrate technological competence development, emotional skill enhancement, and motivational interventions to better prepare students for the evolving labor market.